2015
DOI: 10.14423/smj.0000000000000338
|View full text |Cite
|
Sign up to set email alerts
|

Increased Anesthesia Usage in a Large-Volume Endoscopy Unit: Patient Acuity Is Not the Main Predictor

Abstract: The use of MAC for colonoscopies performed in our endoscopy unit increased significantly from 2003 to 2012. Although increased MAC use was associated with some patient variables, it was most significantly associated with the year of the procedure. This suggests that there were other nonpatient-related factors influencing its use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This might be due to the antiemetic effect of propofol. Studies have reported that propofol and the opioid combination provided not only analgesia and amnesia, but also decreased the frequency of nausea and vomiting (14,22). Nausea and vomiting are the common adverse effects of opioids.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the antiemetic effect of propofol. Studies have reported that propofol and the opioid combination provided not only analgesia and amnesia, but also decreased the frequency of nausea and vomiting (14,22). Nausea and vomiting are the common adverse effects of opioids.…”
Section: Discussionmentioning
confidence: 99%